The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3109/11038128.2015.1020865
|View full text |Cite
|
Sign up to set email alerts
|

Expanding client-centred thinking to include social determinants: a practical scenario based on the occupation of breastfeeding

Abstract: Expanding client-centred thinking to include awareness, understanding, and respect for social determinants of occupation may enhance therapist-client interactions and outcomes of the occupational therapy process, and address gaps in current thinking that may contribute to occupational injustices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
15
0
4
Order By: Relevance
“…Este paradigma rigidiza las prácticas médicas, ejemplo de ello es el establecimiento de horarios para lactar, perjudicando en muchas ocasiones, la adherencia de la lactancia materna exclusiva aumentando la percepción de estrés y descontento en las mujeres madres (Broche Cando et al, 2011). Asimismo, la adaptación ocupacional de las mujeres en el proceso de lactancia materna depende de aspectos fundamentales, tales como sus habilidades sociales y contar con una red de apoyo, tanto familiar como de la pareja, que entregue un soporte emocional durante todo el proceso (Horne et al, 2005;Pitonyak et al, 2015).…”
Section: Repensar Los Roles De Génerounclassified
See 1 more Smart Citation
“…Este paradigma rigidiza las prácticas médicas, ejemplo de ello es el establecimiento de horarios para lactar, perjudicando en muchas ocasiones, la adherencia de la lactancia materna exclusiva aumentando la percepción de estrés y descontento en las mujeres madres (Broche Cando et al, 2011). Asimismo, la adaptación ocupacional de las mujeres en el proceso de lactancia materna depende de aspectos fundamentales, tales como sus habilidades sociales y contar con una red de apoyo, tanto familiar como de la pareja, que entregue un soporte emocional durante todo el proceso (Horne et al, 2005;Pitonyak et al, 2015).…”
Section: Repensar Los Roles De Génerounclassified
“…Esta situación invita a repensar en los roles de género de manera que problematice las condiciones estructurales (Lagarde, 1996) en las cuales hoy en día se desempeña el ejercicio de lactar, así también, contribuye a interpelar los conocimientos desde espacios biomédicos no situados en las mujeres que vivencian este proceso y que se ven sometidas al escrutinio salubrista rígido que omite el carácter cultural que implica la lactancia materna (Massó-Guijarro, 2013), perpetuando disparidades e injusticias ocupacionales en los procesos de salud/enfermedad de las mujeres madres (Pitonyak et al, 2015).…”
Section: Repensar Los Roles De Génerounclassified
“…As the majority of students within higher education programs, such as occupational therapy, come from middle-class backgrounds, the discrepancies between client and practitioner class status can have a significant influence on collaboration and rapport-building due to different perspectives and experiences (Beagan, 2007;Beagan & Chacala, 2012). Class-based cultural differences can impact a practitioner's ability to identify systemic barriers associated with low income (Beagan, 2007;Pitonyak, Mroz, & Fogelberg, 2015). A study conducted on medical practitioners found that practitioners with personal experiences related to low income may be more empathetic towards clients of a lower SES than their higher SES medical peers (Woo et al, 2004).…”
Section: What Are Students Learning? How Do They Perceive Their Profementioning
confidence: 99%
“…Further, client-centered care also does not clearly acknowledge access to care as a core component; access includes the ability to seek and receive care according to patient needs and preferences. Although barriers to access to care are implied to an extent within occupational therapy's view of the greater contexts and environments that affect a client, an explicit appreciation is warranted that occupational therapy services need to be available when and how a client requires them for care to be truly client centered (Gupta & Taff, 2015;Pitonyak, Mroz, & Fogelberg, 2015).…”
Section: Comparing Client-centered and Patient-centered Carementioning
confidence: 99%